STANDARDIZATION OF ANTHROPOGENIC LOAD ON AQUATIC ECOSYSTEMS: ASSESSMENT CRITERIA AND MANAGEMENT DECISIONS - KIREITSEVA, HANNA; TSYHANENKO-DZIUBENKO, ILLIA; KHOMENKO, SVITLANA; PIDVYSOTSKYI, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Aquatic ecosystems are currently under unprecedented pressure from transformational changes characterized by irreversibility and cumulative effects. The intensification of anthropogenic load, climate change, and especially in Ukrainian realities, military actions, has significantly complicated the nature of impacts on surface water bodies. Wetlands require special attention as the most vulnerable components of aquatic ecosystems that perform critically important ecological functions including hydrological regime regulation, water purification, biodiversity maintenance, and carbon sequestration. The aim of this study is to systematize scientific research on theoretical approaches to defining transformational changes in aquatic ecosystems and develop criteria for their assessment to make evidence-based management decisions in environmental regulation and anthropogenic load standardization. A comprehensive analysis of modern theoretical approaches, systematization of scientific literature, and bibliometric analysis of 2835 publications in the Scopus database for the period 1990-2024 were conducted. The results confirmed exponential growth in publication activity since the early 2000s, reflecting the increasing relevance of transformational changes in aquatic ecosystems in global scientific discourse. Subject structure analysis revealed the dominance of ecological sciences (39.6%), significant contributions from social sciences (14.7%), Earth sciences (11.3%), and engineering sciences (9.4%), indicating the interdisciplinary nature of the problem. Transformational changes in aquatic ecosystems are defined as significant, often irreversible changes in the structure, functioning, and ecological stability of aquatic environments caused by natural and anthropogenic factors, leading to the formation of new stable ecosystem states that significantly differ from the initial ones and are characterized by the loss of ability to return to the previous state even after cessation of disturbing factors. A comprehensive system of criteria for assessing transformation of aquatic ecosystems has been developed, including three main groups: hydrological, physico-chemical, and biological indicators with corresponding quantitative indicators for standardizing anthropogenic load. Quantitative transformation indicators have been established: changes in average annual flow >15%, oxygen concentration <6 mg/l, Shannon index decrease >20%, etc. The cumulative effects of major impact factors were analyzed: urbanization, climate change, and military actions. It was established that the combination of different factors creates synergistic effects that significantly exceed simple additive impact. Particularly dangerous are combinations of urbanization with climate change (eutrophication enhancement), urbanization with military actions (complex pollution), and climate change with military actions (ecosystem degradation acceleration). The scientific novelty lies in forming a holistic conceptual framework for understanding transformational changes in aquatic ecosystems and developing approaches to their regulation through permit activities and environmental standards implementation. The practical significance is determined by the possibility of using the results to develop effective water resource management strategies under conditions of multiple stress impacts, optimize permit activities in ecology, and ensure sustainable development of the water management sector through evidence-based decision-making processes.